En lidt overset “queer-person” i Pontoppidans forfatterskab - de Thurah, Christian (Pontoppidaniana, 2024)
Abstract When it comes to female characters in Henrik Pontoppidan´s works, focus is often on either Jakobe Salomon in Lykke-Per (eng. A Fortunate Man) or Jytte Abildgaard in De Dødes Rige (eng. Realm of the Dead) – or both. In this article, Christian de Thurah draws attention to a third female character who appears in two of Pontoppidan´s late works, the play Asgaardsrejen (1906) and the novel Mands Himmerig (1927), Ragna Nordby. This slightly overlooked character is seen here as Pontoppidan´s late attempt to depict a modern, emancipated – even “queer” – female.